THE REFLECTION OF “REPUBLICAN WOMAN” IMAGE IN ATATÜRK PERIOD TO SECOND EDUCATION HISTORY IV COURSEBOOK (Third Sector Social Economic Review, 2021)
The purpose of this research is to examine the image of “Republican Woman” in Atatürk Period and the reflection of this image to the secondary education textbook “Republic of Turkey-History IV”. History IV textbook for secondary education teaches History of Republic of Turkey from year 1931 to 1949. It is one of the four-volume secondary education textbooks which had been prepared by The Society of Research of Turkish History. This study analyzes how History IV textbook handles the “Republican Woman” image which is defined by the Republic within the context of creating a democratic and modern structure of society. This research employs historical research design which is one of the Qualitative Research Methods. The relevant data were collected by using document analysis technique, and they were analyzed specifying the themes with descriptive analysis method. Political, social, economic and military spheres where revolutions were made were defined as themes of this research, and through these themes coding has been done. The textbook teaches the Republican Woman image as an equal, powerful, well-educated, modern identity who should raise children with quality education and who is expected to show presence in every sphere of life. While teaching the topics, various speeches of Atatürk are frequently quoted. The textbook demonstrates that Atatürk gave particular importance to creating a “Republican Woman” image.
Keywords: Atatürk Period; History of Republic of Turkey; women; secondary education